2007
DOI: 10.1007/s00595-007-3500-1
|View full text |Cite
|
Sign up to set email alerts
|

Large Mucinous Cystadenoma of the Pancreas During Pregnancy: Report of a Case

Abstract: A 33-year-old woman, gravida 2, para 1, was diagnosed to have a benign mucinous cystic neoplasm of the pancreas 5 months before delivery. The tumor measured 12 cm in diameter at the time of diagnosis. The antenatal course was uneventful, and a vaginal delivery produced a normal infant. By 2 months after delivery, the tumor reached 18 cm. At surgery, a huge cyst was found to originate from the pancreas, and a distal pancreatectomy with splenectomy was performed. The cystic mass was multilocular 18 x 17 x 12 cm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…In the English literature there are only two reports of patients who delivered vaginally at term [4,5], and in 1 case the tumor was discovered only 2 months after delivery [5]. Of the other 8 PMCNs reported, 7 were resected during the second trimester of pregnancy [6,7,8,9,10,11,12] and one at 34 weeks (due to cyst rupture [13]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the English literature there are only two reports of patients who delivered vaginally at term [4,5], and in 1 case the tumor was discovered only 2 months after delivery [5]. Of the other 8 PMCNs reported, 7 were resected during the second trimester of pregnancy [6,7,8,9,10,11,12] and one at 34 weeks (due to cyst rupture [13]).…”
Section: Discussionmentioning
confidence: 99%
“…Transabdominal fine-needle aspiration is debatable due to the risk of tumor cell seeding [4]. Even if, theoretically, a fine-needle aspiration is done, cytology, tumor markers (CEA, CA 19-9, CA 15-3, CA 72-4, CA 125), enzymes (amylase, lipase) as well as DNA analysis (loss of heterozygosity - LOH and K-ras mutations) from the cyst fluid, have a specificity which varies considerably in different studies [14,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four cases were histologically diagnosed as benign mucinous cystadenoma [3][4][5][6] , while the other four were diagnosed as mucinous cystadenocarcinoma [7][8][9][10] . Our case might be the first case of pancreatic MCN with moderate dysplasia (also referred to as "borderline tumor"), in association with pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic MCNs occur almost exclusively in females, and are potentially sex hormonesensitive, according to the studies reported to date [2] . However, MCNs encountered in pregnancy are rare; only eight such cases have been reported in the English literature [3][4][5][6][7][8][9][10] . In this report, we describe a 30-year-old woman with a large pancreatic MCN that grew rapidly during the early stage of pregnancy.…”
Section: Introductionmentioning
confidence: 99%